Popes and antipopes : the politics of eleventh century church reform - Stroll, Mary (Studies in the history of Christian traditions ;, 2012)
Concentrating on the popes and the antipopes, this book examines the perturbations of ecclesiastical reform from the mid-eleventh century to the reign of Gregory VII, pointing out what factors other than reform influenced the main personae. It demonstrates how a weak papacy reversed power with a strong empire.